Mitigating the Inhibitory Effect of Tannins on β-Glucosidase Activity Using Tannase from Lactiplantibacillus plantarum - Godse, Ravish; Vaidya, Isha; Sharma, Sharoni; Kulkarni, Ram (Bogor Agricultural University, Indonesia, 2025)
Tannins are a diverse group of plant-derived polyphenols with a hallmark property to bind to various biomolecules. Their binding with enzymes in specific ways leads to the loss of their enzymatic potential. A similar phenomenon is postulated in the case of tannins from fruits inhibiting the β-glucosidase activity, causing lesser hydrolysis of glycosidically bound volatiles in fruit juices. We first demonstrated that tannins, viz. tannic acid and epigallocatechin gallate, significantly inhibited β-glucosidase activity. Next, the cell-free supernatant (CFS) of Lactiplantibacillus plantarum, which is known to have tannase activity, was found to de-repress β-glucosidase inhibition caused by tannins. Our results indicate that tannase, along with β-glucosidase, can be a useful strategy for hydrolysing glycosidic phytochemicals for the release of bioactive chemicals.